PENGARUH KOMITMEN ORGANISASI, MOTIVASI EKSTRINSIK DAN KARAKTERISTIK INDIVIDU TERHADAP PRESTASI KERJA PEGAWAI PADA BANK BPD BALI KANTOR CABANG RENON - Kadek Riska Aprilia; I Wayan Sujana; Ni Nyoman Novarini (VALUES, 2022)
Achievement is the result of work in quality and quantity achieved by a person in carrying out his duties, in accordance with the responsibilities given to him. Work performance is a formal procedure carried out within the organization to evaluate employees and contributions and interests of employees. This study aims to examine and obtain empirical evidence of the effect of organizational commitment, extrinsic motivation, and individual characteristics on employee performance at Bank BPD Bali Renon branch office. This research was conducted at Bank BPD Bali Renon branch using a sample of 90 employees. The sampling technique used in this research is the census method. Data was collected through interviews and questionnaires. The data analysis technique used in this study was multiple linear regression which was processed using the Statistical Package Social Science (SPSS) version 23. The results of this study indicate that organizational commitment, extrinsic motivation, and individual characteristics have a positive and significant effect on employee performance at Bank BPD Bali Renon branch office. Things that must be improved are good relations between employees and employees and it is hoped that the company will be able to increase the sense of belonging of an employee so that employees can contribute to the company. Future research is expected not to stick to the factors in this study, namely Organizational Commitment, Extrinsic Motivation and Individual Characteristics in researching, but can add other factors that may affect Employee Performance.